2020
DOI: 10.14740/cr1097
|View full text |Cite
|
Sign up to set email alerts
|

Skin Autofluorescence as a Predictor of First Heart Failure Hospitalization in Patients With Heart Failure With Preserved Ejection Fraction

Abstract: Background: An autofluorescence (AF) reader can be used to diagnose skin AF non-invasively by measuring local accumulation of advanced glycation end-products. A number of studies have investigated the relationships between skin AF and cardiovascular disease. However, data regarding the usefulness of skin AF as a predictor of chronic heart failure remain limited. This prospective study aimed to elucidate the usefulness of skin AF as a predictor of first heart failure (HF) hospitalization in patients with HF wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Waateringe et al reported that, for every unit of SAF increase, the risk of developing CVD increases threefold and the risk of death increases fivefold in a study with 72,880 participants [ 30 ]. Additionally, a study on patients with HF with preserved ejection fraction found that higher SAF levels (SAF > 2.9 AU) were associated with first hospitalization for HF [ 32 ]. Moreover, our teams have recently reported that exercise capacity, a strong predictor in patients with CVD, was significantly lower in patients with higher SAF levels regardless of their DM status and that SAF levels were independently associated with exercise intolerance in patients with CVD [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Waateringe et al reported that, for every unit of SAF increase, the risk of developing CVD increases threefold and the risk of death increases fivefold in a study with 72,880 participants [ 30 ]. Additionally, a study on patients with HF with preserved ejection fraction found that higher SAF levels (SAF > 2.9 AU) were associated with first hospitalization for HF [ 32 ]. Moreover, our teams have recently reported that exercise capacity, a strong predictor in patients with CVD, was significantly lower in patients with higher SAF levels regardless of their DM status and that SAF levels were independently associated with exercise intolerance in patients with CVD [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…SAF may be a prognostic factor in patients with long-standing persistent atrial fibrillation and the risk value of SAF was considered as 2.6 AU for high CHADS2 score and SAF value at 2.7AU for elevated high sensitivity cardiac troponin levels [27]. Furthermore, SAF can predict the risk of the first HF hospitalization in patients with preserved ejection fraction and the cut-off point of SAF was determined to be > 2.9 AU [28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a study by Yoshioka [55], SAF can predict CV risk in patients with T2DM, being correlated with elevated hs-cTnT and NT-proBNP. Another CV risk identified by Hitsumoto [56] is the prediction of the risk of first HF hospitalization in patients with HFpEF.…”
Section: Biologic Biomarkers Associationsmentioning
confidence: 99%